Master Class with Miklós Perényi Verbier Festival 2018 - Brahms, Johannes 1833-1897; Haydn, Joseph 1732-1809; Haydn, Joseph 1732-1809; Beethoven, Ludwig van 1770-1827 (DakApp, 2018)
2018 marked the 25th anniversary of the Verbier Festival, an exciting milestone for Verbier's artists and audiences alike! For the first time, we brought you closer to the musicians than ever before with ten master classes led by incredible artists, including Barbara Frittoli, Thomas Quasthoff, the Quatuor Ébène, Richard Goode and others. Photo: Miklós Perényi © Aline Paley